GE_GERICHTE P/22749/2016 vom 6. März 2018 - GE Cour de justice (2018)
SÉJOUR ILLÉGAL ; TRAVAIL AU NOIR ; EXEMPTION DE PEINE ; ÉGALITÉ DE TRAITEMENT | LEtr.115.al1.letb; LEtr.115.al1.letc; CP.52; CPP.8; Cst.8